2018
DOI: 10.1111/pan.13530
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral and thoracolumbosacral cerebrospinal fluid volume changes in neonates, infants, children, and adolescents: A retrospective magnetic resonance imaging study

Abstract: Summary Background The volume of cerebrospinal fluid can affect the pharmacokinetics and pharmacodynamics of local anesthetics for spinal anesthesia and other intrathecal medications. Aims The objective of this study was to estimate the lumbosacral cerebrospinal fluid volume and thoracolumbosacral cerebrospinal fluid volume using magnetic resonance images in pediatric patients from neonates and infants to adolescents. Methods Spinal magnetic resonance images of 500 pediatric patients (age <18 years) were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…12,22 More recently, magnetic resonance imaging studies have shown CSF volumes in children that correlate with changes in height, age, and weight, but that are smaller than previously estimated. 23 Nonetheless, these physiologic mechanisms support the requirement for a higher dose of bupivacaine (0.8-1 mg/kg) than older children and adults. There are multiple studies examining the variation in local anesthetic dose requirements as infants age and gain weight.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…12,22 More recently, magnetic resonance imaging studies have shown CSF volumes in children that correlate with changes in height, age, and weight, but that are smaller than previously estimated. 23 Nonetheless, these physiologic mechanisms support the requirement for a higher dose of bupivacaine (0.8-1 mg/kg) than older children and adults. There are multiple studies examining the variation in local anesthetic dose requirements as infants age and gain weight.…”
Section: Discussionmentioning
confidence: 96%
“…Infants and neonates have different intrathecal pharmacodynamics and pharmacokinetics compared to adults because of a higher cerebrospinal fluid (CSF) volume, higher heart rate, increased CSF flow and turnover, larger volume of distribution, and greater clearance 12,22 . More recently, magnetic resonance imaging studies have shown CSF volumes in children that correlate with changes in height, age, and weight, but that are smaller than previously estimated 23 . Nonetheless, these physiologic mechanisms support the requirement for a higher dose of bupivacaine (0.8‐1 mg/kg) than older children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, two cases of PDPH (1%) were diagnosed in children aged 4 and 5 years in whom a 22G cutting spinal needle had been used. Using 25 G needle with a noncutting tip is therefore recommended as using larger needles, and cutting tips may be associated with a PDPH incidence up to 15% 11–12,16,30–32 …”
Section: Discussionmentioning
confidence: 99%
“…Nusinersen is administered intrathecally in periodic doses of 12 mg in 5 ml independently from patients' age or height. Because height was shown to be related to spinal CSF volume [45,46], smaller individuals may attain higher drug levels relative to their CSF volume. In the course of treatment, we observed monocytic cells with indefinable, unspecified inclusions within the nusinersen-treated cohort of Dresden.…”
Section: Discussionmentioning
confidence: 99%